Communication of Corporate Social Responsibility Activities by Private Sector Companies in India: Research Findings and Insights. Issue 2 (July 2015) - Ghosh, Sumona
This paper aims to explore in to the aspect of establishment of a pattern of participation of CSR activities amongst the private sector companies as reflected in the respective company documents in the public domain, taking rate of growth of profit as the parameter.An empirical and analytical study was undertaken whereby the corporate official websites of the companies were analyzed .Data was then generated from such an analysis using Qualitative Document Analysis. For this study we used "number of sentences" as the unit for measurement of CSR participation. Descriptive statistics, Pearson's Correlation, multiple regression analysis and conjoint analysis were the tools used for the study. It was noticeable that with respect to private sector companies in India attitude towards CSR communication is in a confused state where, the business community has shown its responsiveness towards communication of various CSR activities but the level of importance that was attached to such activities was not uniform across deciles, deciles being characterized by growth rate of profit. Responsiveness and inspirations to involve in CSR activities and its communication do not seem to show any particular association with growth rate of profit. The association seems to be haphazard, so nothing concrete could be concluded at this stage.